Geochemistry of Holocene sediments from Chilika Lagoon, India: inferences on the sources of organic matter and variability of the Indian summer monsoon. (20th October 2021) - Amir, Mohd; Paul, Debajyoti; Malik, Javed N.
Abstract: We present bulk organic carbon isotopic composition (δ 13 C), total organic carbon (TOC) content, and total organic carbon to total nitrogen (C/N) ratio along with major and trace element geochemistry of an AMS radiocarbon-dated Holocene sediment core collected from Chilika Lagoon, India. The data are used to understand changes in the organic matter (OM) sources and the strength of the Indian summer monsoon (ISM). Our results indicate that during early to middle Holocene (10.4–4.9 ka), terrestrial (23–65%) and macrophyte (24–32%) sources were significant contributors to the sediment OM; marine component contributed ≤23%. An abrupt shift in the OM sources was observed at 4.0 ka, marked by a significant decrease in OM contributions from the terrestrial (5%) and macrophyte (14%) end-members, and an increase in the marine end-member source (70%) into the lagoon. The period from 4.0 to 2.1 ka recorded the lowest and highest contribution from the terrestrial (5–11%) and marine (50–70%) sources, respectively. This was followed by a gradual increase in the terrestrial and decrease in the marine contribution to 21% and 25% till the present, respectively. During this period, phytoplankton became the major source (31–40%) of OM to the lagoon. This period also experienced increasing anthropogenic activities in the catchment. In this study, proxy records show a strong ISM during early Holocene (10.4–9.0 ka), which was followed by a gradual weakening until 4.9 ka. At 4.0 ka, an abrupt and pronounced weakening of ISM occurred that was followed by an amelioration of ISM precipitation towards 1.1 ka. Later, the ISM gradually weakened to the present-day condition. Overall, Chilika Lagoon core records exhibit that changes in the Northern Hemisphere summer insolation regulate the long-term trend of ISM during the Holocene.